Global Halal industry: realities and opportunities - Abdullah, Moha Asri; Azam, Md. Siddique E. (2019)
The global industry as a whole is estimated to worth around USD2.3 trillion (excluding Islamic finance) a year. It is now one of the fastest growing markets. The global market growth is estimated to reach at an annual rate of 20 percent per annum. The global halal market of 2.18 billion Muslims is no longer confined Muslims only. Similarly, the Halal industry is no longer confined to food and food-related products, but rather to include pharmaceuticals, cosmetics, health products, toiletries and medical devices as well as service sector components such as logistics, marketing, print and electronic media, packaging, branding, and financing. This paper attempts to examine the current realities of the global halal industry by observing factors determining such increasing demand for Halal industry, in addition to opportunities that are offered from on recent global development in the market. The word halal is rooted from an Arabic word which means ‘permissible’ or ‘lawful’ according to the Islamic rules and regulations. The concept of halal is not bound to food-related items only but to multiple other aspects such as products, which can be further categorized into various groups, for instance, cosmetics, self-care, health, tourism and services. A global survey discovered that the Muslims spend on food, beverages and lifestyles amounting to USD$2 trillion in 2016. Moreover, the global Muslim market spends on travel reaching USD$169 billion in 2016 and expected to increase to USD$283 billion in 2022. Meanwhile, the Muslim average per capita income (GDP) has risen from USD$1763 to USD$6530 from 1993 to 2010. The findings show that there are three major factors driving the rapidly growing global halal market. First, sizable and growing Muslim population at 1.8 per cent per annum, Second, growing economic development and hence increasing purchasing power among the Muslim. Last, emergence of the potential halal market in non-Muslim nations but visible Muslim population. Nonetheless, numerous challenges confronting Halal industry players. These include the standardization of halal, lack of data, animal right, halal is not compulsory in many Muslim countries and others. As a way forward, industry players need to deepen knowledge and understanding of the Muslim market (pattern and behavior), regularly update data, and exploit untapped market niches as well as product sales and promotion.